Fasting blood glucose-to-glycated hemoglobin ratio for evaluating clinical outcomes in patients with ischemic stroke - Shao, Tengfei; Liu, Hui; Yang, Guochao; Wang, Huan; Li, Di; Ni, Huanyu; Xu, Yun; Zhang, Jinping (Frontiers in Neurology, 2023)
Background Stress hyperglycemia frequently occurs in patients with acute ischemic stroke (AIS). The influence of stress hyperglycemia on the outcomes of patients with AIS remains ambiguous. Methods Data from our institution on patients with AIS between June 2020 and June 2021 were retrospectively analyzed. The severity of the stroke was assessed using the National Institutes of Health Stroke Scale (NIHSS) at admission, and the primary endpoint was functional outcomes. Stress hyperglycemia was measured by the glucose-to-HbA1c ratio. In the multivariable analysis, two models that retained or excluded the NIHSS were adopted to explore the relationship between stress hyperglycemia and outcomes. The receiver operating characteristic curve (ROC) was calculated to determine an optimized cutoff value. Results The optimal cutoff value was 1.135. When all patients were included, model 1 did not find an association between the glucose-to-HbA1c ratio and functional outcomes. In model 2, the glucose-to-HbA1c ratio×10 (Glucose-to-HbA1c ratio ×10) was the independent predictor of functional outcomes (OR 1.19, 95% CI 1.07–1.33, p < 0.01). Separately, in patients without diabetes, the glucose-to-HbA1c ratio×10 was the independent predictor of functional outcomes in both model 1 (OR 1.37, 95% CI 1.08–1.73, p = 0.01) and model 2 (OR 1.48, 95% CI 1.22–1.79, p < 0.01), but not in patients with diabetes. In addition, the glucose-to-HbA1c ratio×10 was the independent predictor of stroke severity (OR 1.16, 95% CI 1.05–1.28, p < 0.01). Conclusion The glucose-to-HbA1c ratio was associated with more severe AIS. Specifically, the glucose-to-HbA1c ratio was associated with the functional outcomes in patients without diabetes but not in patients with diabetes.